PROCESSING MICROPOROUS CARBON ADSORBENTS BY PHYSICAL AND CHEMICAL TREATMENTS FOR GAS SEPARATION - Herawan, Safarudin Gazali (2000)
Processes have been developed for producing microporous carbon adsorbents which are suitable for separating carbon dioxide from methane in a gas stream. A carbonaceous starting material, oil palm shell, has been used in the process to obtain various type of adsorbents for gas adsorption applications. The products include char, activated char and carbon molecular sieve, which were produced from different optimal processing systems. Pyrolysis, physical and chemical activation have been applied for the manufacturing of the products. The adsorbents have been veriﬁed for its physical characteristics using molecular probe analytical method. A gas chromatography unit and a single bed adsorber have been used to test and compare the gas separation performance of the products. The adsorption kinetics on CO3 and Cl-l.| were recorded in the breakthrough curves. The products have shown a great feasibility in gas separation and are useful and economical for chemical processing industries, especially in pressure swing adsorption applications.